In Virto Antioxidant Activities of New 4,5-Dihydro-1H,2,4-triazol-5-ones having Thiophene Ring with their Acidic Properties - H. Yuksek; F. Islamoglu; O. Gursoy Kol; S. Bahceci; M. Bekar; M. Aksoy (E-Journal of Chemistry)
Seven new 3-alkyl(aryl)-4-(2-thienymethylenamino)-4,5-dihydro-1H-1,2,4-triazol-5-ones (2) were synthesized by the reactions of 3-alkyl(aryl)-4-amino-4,5-dihydro-1H-1,2,4-triazol-5-ones (1) with thiophene-2-carbaldehyde. In addition, N-acetyl derivatives of compounds 2d-2g were also prepared. The structures of eleven new compounds synthesized were determined by elemental analysis as well as IR, NMR and UV spectral data. In addition, compounds 2a-g and 3a, 3b, 3d-f were also screened for their antioxidant activities and 2a-g were potentiometrically titrated with tetrabutylammonium hydroxide (TBAH) in four nonaqueous solvents (isopropyl alcohol, t-butyl alcohol, acetonitrile and N,N-dimethyl formamide). Also half-neutralization potential values and the corresponding pKa values were determined in all cases.